2007
DOI: 10.1007/s11103-007-9229-9
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid profiling among wild type and related GM wheat varieties

Abstract: Pleiotropic effects are one of the main concerns regarding genetically modified organisms (GMOs). This includes unintended side effects of the transgene or its genome insertion site on the regulation of other endogenous genes, which could potentially cause the accumulation of different secondary metabolites that may have not only an impact on diet as repeatedly worried by the public but also on the environment. Regarding amount and possible environmental effects, flavonoids represent the most prominent group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 42 publications
7
42
0
Order By: Relevance
“…Moreover, the fragmentation pathway of the base peak at m/z 449 corroborated the hypothesis of a luteolin-C-glucoside derivative (Ioset et al, 2007) and the loss of 132 Da from the product ion at m/z 449 confirmed the presence of a pentose unit with a O-linkage (Cuyckens & Claeys, 2004;Han et al, 2008;Regos, Urbanella, & Treutter, 2009;Ye, Yan, & Guo, 2005). Overall, the above results allowed the detection, for the first time, of two isomers of 2 00 -O-pentosyl-C-hexosyl-luteolin derivatives in Cytisus.…”
Section: Luteolin Derivativessupporting
confidence: 74%
“…Moreover, the fragmentation pathway of the base peak at m/z 449 corroborated the hypothesis of a luteolin-C-glucoside derivative (Ioset et al, 2007) and the loss of 132 Da from the product ion at m/z 449 confirmed the presence of a pentose unit with a O-linkage (Cuyckens & Claeys, 2004;Han et al, 2008;Regos, Urbanella, & Treutter, 2009;Ye, Yan, & Guo, 2005). Overall, the above results allowed the detection, for the first time, of two isomers of 2 00 -O-pentosyl-C-hexosyl-luteolin derivatives in Cytisus.…”
Section: Luteolin Derivativessupporting
confidence: 74%
“…Red MYB transcription factor PAP1 resulted in accumulation of cyanidin and quercetin derivates and led to the activation of genes associated with the anthocyanin production (Tohge et al, 2005). Figure 4C shows a schematic pathway outline of the conserved flavonoid biosynthesis pathway, including anthocyanin, flavonol, glycoflavone, and isoflavone synthesis, based on literature survey and KEGG pathways, for Arabidopsis (Tohge et al, 2005(Tohge et al, , 2007Yonekura-Sakakibara et al, 2008), barley (Nørbaek et al, 2003;Brazier-Hicks et al, 2009;Klausen et al, 2010), Medicago (Kowalska et al, 2007;Farag et al, 2008), rice (Han et al, 2009;Kim et al, 2009), soybean (Steele et al, 1999;Choung et al, 2001;Latunde-Dada et al, 2001), and wheat (Ioset et al, 2007). Subclasses of flavonoids and anthocyanins have been detected and reported in all six plant species, but none of the flavonoid subfamilies, flavonol, glycoflavone, and isoflavone, has been reported.…”
Section: Flavonol and Flavonoid Synthesis: Chssmentioning
confidence: 99%
“…This highlights the necessity of careful interpretation of microarray results when extensive progressive developmental changes occur, as is the case for seeds, and when minor asynchrony is hard to avoid. Ioset et al (2007) analyzed lines with either a combination of three transgenes or a single one (KP4, of viral origin) for increased defense against fungal pathogens. For greenhouse-grown plants, they found only minor differences in the flavonoid profile between GE lines and their conventional control lines.…”
Section: Peamentioning
confidence: 99%